Model of knowledge and creativity in process engineering. A popperian approach to development of human mind products - Acevedo Borrego, Adolfo (2015)
Creativity is an essential element of scientific management where decisions are made by rational paradigm that involves the use of convergent criteria in the management, organization and hierarchy of problems. The process engineer emphasizes the systematic and rational side, which is the visible and concrete engineer’s work. The invisible part constitutes the heuristic and creative side, comprising the imaginative and divergent view that complements the first and develops as new tasks arise in the areas of research and design, which requires vision and innovation. This paper aims to highlight the creativity of engineers. They have taken their creative products whose description and study, must lead to identifying new ways of seeing reality, beyond traditional approaches, and understand the orientation of creativity, to improve understanding and problem solving. Creativity in industrial engineers is based largely on True knowledge of reality which seems consistent with academic formation focused on managing reality to change and improve it, for the benefit of society.